2017
DOI: 10.1016/j.geomphys.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Norm-square localization for Hamiltonian LG-spaces

Abstract: Abstract. We prove a formula for twisted Duistermaat-Heckman distributions associated to a Hamiltonian LG-space. The terms of the formula are localized at the critical points of the norm-square of the moment map, and can be computed in cross-sections. Our main tools are the theory of quasi-Hamiltonian G-spaces, as well as the Hamiltonian cobordism approach to norm-square localization introduced recently by Harada and Karshon. IntroductionLet M be a Hamiltonian G-space with moment map φ : M → g * , and equip g … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The latter motivated us to define the 'quantization' of (M, L) as this particular element of R k (G). In a related paper [27], the first author showed that this definition agrees with that of E. Meinrenken [38] based on quasi-Hamiltonian spaces and twisted K-homology.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The latter motivated us to define the 'quantization' of (M, L) as this particular element of R k (G). In a related paper [27], the first author showed that this definition agrees with that of E. Meinrenken [38] based on quasi-Hamiltonian spaces and twisted K-homology.…”
Section: Introductionsupporting
confidence: 57%
“…If ξ, ζ ∈ Lg ⊥ µ ⊆ Lg, the second term in (21) does not contribute, while the first term is given by (20). We conclude that the given metric on ker(T q) z = Lg differs from the metric (20) only on a finite-dimensional subspace.…”
Section: It Remains To Provementioning
confidence: 73%
See 2 more Smart Citations
“…The first type is a non-abelian localization formula (Theorem 3.19), which shows that the index is expressible as a sum of contributions localized near the components of the critical set of the norm-square of the moment map µ M : M → Lg * . There is a large literature on non-abelian localization in various forms, for example [39,65,61,72] amongst many others; in the more specific context of Hamiltonian loop group spaces references include [24,76,43,48,44]. We prove non-abelian localization by adapting a technique of Bismut-Lebeau [21, Chapter IX] to analyse the resolvents of a 1-parameter family of operators in the limit as the parameter goes to infinity.…”
Section: Introductionmentioning
confidence: 99%